Zero-voltage switching bi-directional isolated LLC resonant DC/DC converter for wide voltage gain and load range / S.M. Showybul Islam Shakib - S.M. Showybul, Islam Shakib (2017)
Bi-directional DC/DC converters (BDCs) are widely used in many electric power applications such as automobiles, electric vehicles, renewable energy sources, uninterrupted power supplies (UPS), DC micro grid with energy storage systems (ESSs) and so on. Among all the BDCs, Bi-directional resonant DC/DC converters (BDRDCs) are considered as the best suitable for minimizing the switching losses, reducing electromagnetic interference and achieving high frequency operation ability. However, BDRDCs have the inherent limitation of zero voltage switching (ZVS) operation for a wide variation of load and input voltages. This study presents an isolated bi-directional LLC series resonant DC/DC converter with novel frequency adaptive phase shift modulation (FAPSM) control, which is capable of maintaining ZVS for wide variation of load and input voltages. This topology is composed of a stacked structure where four switches are connected in series but sharing the same resonance tank and high frequency transformer. The voltage stress across each switch is reduced to half of the input voltage due to the series combination of four switches. It also uses an active rectifier in the secondary side of the transformer and becomes the key component of an energy storage system (ESS) to enable the bi-directional power flow. The proposed control is composed of two control variables: switching frequency and phase shift angle of the secondary switches. The Switching frequency changes with the load in such a way that, it is secured ZVS to the primary side switches for all phase shift angles. Automatically, it maintains the converter gain characteristics identical regardless of load conditions for all phase shift angles. On the other hand, the phase shift changes according to the input variations only. Thus the converter maintains ZVS to all switches for wide voltage gain and load range. The control also makes the converter voltage gain independent of the loaded quality factor. The simultaneous use of two control variables also reduces the circulating current (or reactive power), especially at light load conditions. In addition, Frequency selection for each load condition helps to minimize the series RMS resonance current as compared to fixed frequency operation which improves the light load efficiency significantly. Furthermore, high value of magnetizing inductance is designed (which has no effects on voltage gain) in this converter, which reduces the conduction losses as well as increases the efficiency of the converter. Experimental results of a 1kW prototype converter with 200-400V input and 48V output are presented to verify the performance of the proposed converter. The measured efficiency of the converter at full load condition is 96.5% and 92% for maximum and minimum input voltage respectively during power flow in forward direction.